2014
DOI: 10.1227/neu.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Treatment of Complex Unruptured Cavernous and Paraclinoid Aneurysms

Abstract: Treatment of these aneurysms can be carried out with acceptable rates of morbidity. Careful patient selection is crucial for optimal outcome. Endovascular treatment volumes likely will continue to predominate over microsurgical techniques as changing skill sets evolve in neurosurgery, but individualized application of all available treatment options will continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Previous studies focused on the treatment of large and giant wide-necked aneurysms between the petrous and cavernous segments of the ICA, for which the PED was approved originally. 4,6,24,37,40,46 These promising results led to increasing off-label use of the PED for aneurysms that are not large and not wide necked, and several groups have found similarly strong results after treating small aneurysms 11,17,26 and other off-label applications. 2,10,13,28,32,36 Still, the number of studies on use of the PED to treat small aneurysms has been limited, and very few have directly compared patient outcomes with those of patients after coiling or clipping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies focused on the treatment of large and giant wide-necked aneurysms between the petrous and cavernous segments of the ICA, for which the PED was approved originally. 4,6,24,37,40,46 These promising results led to increasing off-label use of the PED for aneurysms that are not large and not wide necked, and several groups have found similarly strong results after treating small aneurysms 11,17,26 and other off-label applications. 2,10,13,28,32,36 Still, the number of studies on use of the PED to treat small aneurysms has been limited, and very few have directly compared patient outcomes with those of patients after coiling or clipping.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate the findings of these studies and also provide data from a direct comparison of PED placement to coiling and clipping among patients treated over a 6-year period. In 1 of the few other comparative studies, Kim et al 26 reported the treatment of 24 paraclinoid aneurysms with PED placement, 24 with clipping, and 41 with stent-assisted coiling. Treatment with a PED resulted in complete aneurysm occlusion in 81% of the patients, and they found a 13% rate of posttreatment cranial nerve palsy, compared to a 0% rate after coiling and a 29% rate after clipping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraclinoid aneurysms are increasingly being treated with flow-diversion stents, which may further reduce the procedural risks associated with endovascular treatment. [22][23][24][25] Angiographic and clinical outcomes from previous studies are summarized in Table 7. The immediate complete occlusion rate in our series was low (9.5%) compared with those in earlier studies (28.2%-86.6%).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10,17,18,25 It is important to differentiate the exact location of the paraclinoid aneurysm, whether intradural or not, when considering treatment options. The distal dural ring (DDR) is the anatomical boundary between the intra-and extradural segments of the internal carotid artery (ICA) in the paraclinoid region.…”
mentioning
confidence: 99%